2009
DOI: 10.1016/j.dental.2008.10.004
|View full text |Cite
|
Sign up to set email alerts
|

Weakening of dentin from cracks resulting from laser irradiation

Abstract: Cracking of tooth structure is a frequent mechanism of clinical failure necessitating treatment. Some laser conditions, particularly those without sufficient water cooling, may cause surface cracking of dentin. Surface cracks may serve as initiation sites for the onset of catastrophic fracture under mechanical stress, resulting in failure of the dentin. In this study, the hypothesis that laser initiated cracks result in lower bending strength of dentin was tested. Dentin beam specimens were prepared from human… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
39
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(42 citation statements)
references
References 18 publications
1
39
0
1
Order By: Relevance
“…This means that if the temperature is not increased only for a short period of time (few microfractions of a second) heat accumulation can happen and cause ablation, melting, or cracking of tissue. 25 Such unwanted effects were also observed here. In addition to the significant increase of enamel resistance to erosion, the laser parameters tested in the present study have shown, under SEM and higher magnification, some surface modification.…”
Section: Discussionsupporting
confidence: 56%
“…This means that if the temperature is not increased only for a short period of time (few microfractions of a second) heat accumulation can happen and cause ablation, melting, or cracking of tissue. 25 Such unwanted effects were also observed here. In addition to the significant increase of enamel resistance to erosion, the laser parameters tested in the present study have shown, under SEM and higher magnification, some surface modification.…”
Section: Discussionsupporting
confidence: 56%
“…The apparent subsurface flaw lengths resulting from the bur and abrasive air-jet treatments in this approach are 70 µm and 45 µm, respectively. While smaller than the values documented for laser preparation of dentin (Staninec et al, 2009), they caused a significant reduction in the fatigue resistance. Thus, small flaws introduced during the cutting of dentin are detrimental to its durability.…”
Section: Discussionmentioning
confidence: 65%
“…An evaluation of the strength of dentin after laser preparations showed that cracks exceeding 100 µm in length were introduced within the dentin under some treatment conditions (Staninec et al, 2009). Thus, flaws introduced with dental burs are potentially too small to see in direct evaluations (i.e., microscopy), but they could cause degradation in strength if they reach an adequate size.…”
Section: Introduction Tmentioning
confidence: 99%
“…Tooth fracture is more likely to originate from cracks that initiate and grow within the dentin. Flaws in the form of cracks can be introduced within the dentin during the restorative process as a result of material removal [25,26]. As an alternative, cracks may develop in dentin from incipient flaws as a result of fatigue, particularly in regions of stress concentration posed by the restoration geometry [21].…”
Section: Fracture Properties Of Dentinmentioning
confidence: 99%